2007
DOI: 10.1007/s10230-007-0006-4
|View full text |Cite
|
Sign up to set email alerts
|

Mine Water Discharge and Flooding: A Cause of Severe Earthquakes

Abstract: Severe earthquakes can be triggered by dewatering and flooding of mines, as these activities alter the loading of the Earth's crust and tectonic stresses in its interior. Worldwide, more than 200 studies have noted sites where human-induced stresses could have reactivated preexisting faults, triggering earthquakes with seismic moment magnitudes of up to M = 7 on the Richter scale. This can only occur where faults are already under high tectonic stresses that have built up over many years. Stable continental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…The earliest entry in HiQuake, from 1868, is coal mining near Maitland, Australia (Klose, 2007a;2007b). Seismogenic projects are reported from ~70 countries (Fig.…”
Section: Initial Observationsmentioning
confidence: 99%
“…The earliest entry in HiQuake, from 1868, is coal mining near Maitland, Australia (Klose, 2007a;2007b). Seismogenic projects are reported from ~70 countries (Fig.…”
Section: Initial Observationsmentioning
confidence: 99%
“…The increasing depth of mines results in significant increase of groundwater inrush from the underlying aquifers through natural or mine-associated fractured zones or tunnels, which has also contributed to these accidents (Wanfang 1997a;Wu et al 2004;Yin and Zhang 2005;Zhang 2005;Klose 2007). Among the reported accidents in coalmines in China, more than 90% are related to limestone aquifers, including the Ordovician karst aquifers (Shi and Singh 2001).…”
Section: Introductionmentioning
confidence: 95%
“…For areas at risk of water inrush, blockage by grouting in working face, and dewatering the aquifer ahead of working face, could be used to lower the risk of water inrush. In addition, Wang and Park and Klose suggested that mining activities could cause a significant increase in groundwater inrushes into mines from aquifers, through natural or mining-related fractured zones [19,20]. Yin et al and Zhou et al found that mine water inrush was related to fault activation, caused by mining.…”
Section: Introductionmentioning
confidence: 99%